Alunos com deficiência na educação de jovens e adultos em assentamentos paulistas: experiências do PRONERA - Gonçalves, Taísa Grasiela Gomes Liduenha (Universidade Federal de São Carlos, 2014)
The history of our country has shown conflicts over land distribution within a context of social inequality and neglect of the public policies. The production in the area of special education that treats people with disabilities living in the countryside is scanty; although legislation guarantees this legitimate right and the official data indicate the existence of such population. Furthermore, the illiteracy rate is high in our country. If we associate the condition of the disabled youngsters and adults living in rural areas, the situation becomes more alarming. Historically, social movements have played significant actions in our country, such as the claim for public policies to eliminate or reduce illiteracy for those who had no access and permanence during school age. It was created in the countryside the National Education Program in Agrarian Reform (PRONERA) which presents for Adolescents and Adults (EJA) a project developed in partnership with higher education institutions and the National Institute of Colonization and Agrarian Reform (INCRA). Recently, the state of São Paulo, PRONERA has set a partnership with the Universidade Metodista de Piracicaba (UNIMEP), the INCRA and the Organization of Women Settled and Quilombolas of the State of São Paulo (OMAQUESP) in order to develop the EJA project. Thus, the aim of this study was to analyze the educational status of the young adults with disabilities in the countryside. The specific objectives were: analyze the interfaces, Special Education, EJA and the Countryside education, social indicators, within legislation and in academic research; analyze the history of special education, adult education and the Countryside Education to understand the difficulties encountered in the process of education of the disabled, illiterate population who live in rural areas; analyze the history and structure of PRONERA, with particular reference to the EJA; analyze under the focus of special education the organization of an EJA school project from PRONERA developed in two settlements in São Paulo. The study was based on critical pedagogy and its principles. The methodological procedures were guided in: 1) collection and analysis of social indicators, especially the school census, the academic literature and legislation; 2) historical analysis of special need education, adult education, the Countryside Education; 3) document analysis of PRONERA, the initial design and the EJA project report conducted in the state of Sao Paulo; 4) interviews with members of the settlements and people who participated in the project of the EJA from PRONERA. The results showed that despite the legislation and social indicators reveal the interface, there is no academic research on young and disabled adults who live and study in the countryside. Once the story of these three themes is marked by the social exclusion organized into targeted policies such as PRONERA, that intending to correct the process of exclusion of the rural population, makes a mistake in silencing over the educational issues involving students with special educational needs. Thus, relating the settlements, the EJA is developed in precarious conditions; therefore, it does not provide specialized educational services to young people and disabled adults who are getting this type of education in the settlements. It is hoped that this study may support the debate over the right to education for all students and promote the knowledge production about the actual living conditions of people with disabilities living in the countryside.
Keywords: Educação de jovens e adultos; Educação do campo; Assentamentos rurais; Brasil - Programa nacional de educação na reforma agrária; Special education; Youngsters and adults; Countryside education; Settlement; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL